A framework to guide the optimal development and use of real-world evidence for drug coverage and formulary decisions. (14th November 2018) - Pearson, Steven D; Dreitlein, William B; Towse, Adrian; Hampson, Grace; Henshall, Chris
Aim: To provide a framework for optimizing the development and use of real-world evidence (RWE) in drug coverage decisions.Materials & methods: The Institute for Clinical and Economic Review convened a Policy Summit with representatives from 23 payer and life science companies that compose the Institute for Clinical and Economic Review membership.Results: Summit participants helped refine a new conceptual framework that emphasizes the central role of contextual considerations and the evidentiary argument that the RWE is intended to support in designing the process for the development and interpretation of RWE.Conclusion: This framework may provide a structured way for pharmaceutical manufacturers and payers to develop a shared understanding of the best way to develop RWE that will ultimately be useful in informing coverage and formulary decisions.